Cleaning-in-place station decomposition for object-oriented control - Polupan, Volodymyr; Pupena, Oleksandr; Mirkevych, Roman; Klymenko, Oleh; Mirkevych, Oleksii (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers a CIP station used for automated cleaning of process equipment in the food industry. The task addressed relates to the lack of a formalized methodology for decomposing a CIP station that would enable the construction of object-oriented control models in accordance with international standards. The result of this study is the devised methodology for CIP station decomposition based on the principles of IEC 61512, which includes the identification of the levels of process cell, process units, equipment modules, as well as control modules. It has been shown that this approach allows for a structured representation of the equipment and its functions, enabling the integration of technological steps with the equipment of the CIP station. The results are attributed to the fact that the CIP cleaning process has a hierarchical structure and procedural repeatability, which allows it to be formalized as a set of interrelated levels – from the process cell to individual equipment modules. This feature ensures consistency between the process logic and the physical structure of the equipment, which enhances the efficiency of control. A distinctive feature of the results is the combination of hardware hierarchy with information models, which differentiates the proposed solution from conventional descriptive approaches. This not only improves the flexibility and scalability of control systems but also creates conditions for building libraries of reusable software objects. The results could be practically implemented at industrial enterprises in the food, pharmaceutical, and chemical industries where CIP stations are used. They could be integrated into current SCADA/PLC systems using AutomationML and OPC UA standards, ensuring compatibility with MES/ERP levels of control. This improves the efficiency of equipment operation while reducing the costs for designing and maintaining automation systems